Implementasi Kebijakan Penataan Pedagang Kaki Lima - Alfi Huurin’iin; Sri Wibawani (Public Policy : Jurnal Aplikasi Kebijakan Publik dan Bisnis, 2023)
Street vendors (PKL) constantly use the shoulder of the road on Jalan Raya Juanda Airport. It is known that they have violated theSidoarjo Regency Regional Regulation No. 3 of 2016 article 21 paragraph (h) and paragraph (i). The purpose of this study is to describe the implementation of the street vendor arrangement policy on the Juanda Airport main road. Using a descriptive qualitative method with a focus based on the theory of the determinants of policy implementation by Agustino. Data collection techniques using observation, interviews and documentation. Data analysis techniques use the Miles and Huberman interactive model. The results of the study state that 2 determinants have succeeded in influencing policy implementation, namely (1) contrary to the existing value system and (2) membership of a person or group of people in an organization, while 8 factors have been less successful, namely: (1) respect of community members for government authority and compliance; (2) awareness to accept the policy; (3) whether or not there is a legal sanction; (4) personal or group interests; (5) the form of selective compliance; (6) time; (7) socialization; (8) coordination between agencies or between organizations. In general, it can be concluded that only 2 critical success factors have succeeded in influencing implementation and 8 factors have been less successful in influencing the implementation of street vendor management policies.